RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM AND REPLICATIVE CELLULAR SENESCENCE: THEIR INTERACTION DURING THE VASCULAR AGEING - V. S. Pykhtina; I. D. Strazhesko; M. V. Agaltsov; O. N. Tkacheva (Столичная издательская компания, 2015)
The problem of vascular aging is discussed. Special attention among the signs of vascular aging is paid to the activation of the renin-angiotensin-aldosterone system as a source of chronic inflammation and oxidative stress, as well as to its relation to replicative cellular senescence. Potential routes of exposure to these processes are also considered.